Design of an energy storage system for solar panels - Wang, Yu. (2011)
Renewable energy such as solar energy opens up the opportunity for a more decentralized energy supply and decreases the environmental problem caused by the fossil fuel. Integrating renewable energy into conventional distribution system is one of the most effective solutions to apply renewable energy. A distribution network consists of renewable energy resources, power electronic devices, energy storage system and loads, operated either connected to the grid or islanded. The aim of this report is to provide models and simulations studies of an energy storage system for solar penal, including PV generation system, battery, converters and inverters, load and supply source. The controller is designed to control the voltage and power flow of the entire system. The system performance under stand-alone and grid-connected conditions is studied and the data is recorded to study how the PV/battery system works. Finally the energy storage system can work smoothly through changing the charging/discharging status of the battery according to the load demand.